Synthesis of β-Amido Phosphine Oxides and N-(1-oxo-2- diphenylphosphinoyl) Ethyl-4-substituted-2-oxazolidinones by using Arbusov Reaction - SEKHRI, LAKHDAR (Asian Journal of Chemistry, 2010)
A number of α-amino-acids (8a-c) have been used as precursors to prepare the corresponding 4-substituted-2-oxazolidinones (9a-c). N-chloroacetylation of these oxazolidionenes followed by the reaction of Michaelis-Arbusov rearrangement using methoxy diphenyl phosphine provides an efficient and simple method for preparing optically active β-amido-phosphine oxides (5a-c) and N-(1-oxo-2-diphenylphosphinoyl) ethyl-4-substituted-2-oxazolidinones (6a-c) in good overall yields.